Reliability of a revised NOTECHS scale for use in surgical teams. - Sevdalis, N; Davis, R; Koutantji, M; Undre, S; Darzi, A; Vincent, C (2008)
BACKGROUND: Recent developments in the surgical literature highlight the need for assessment of nontechnical skills in surgery. We report a revision of the NOn-TECHnical Skills (NOTECHS) scale of the aviation industry for use in surgery and detailed analysis on its reliability. METHODS: The original NOTECHS scale assesses (1) Cooperation, (2) Leadership and Managerial Skills, (3) Situation Awareness and Vigilance, and (4) Decision Making. We added a Communication and Interaction dimension and adapted all subscales for use in surgical context. Reliability was assessed in simulation-based training for trainee clinicians. RESULTS: Satisfactory reliability (Cronbach's alpha) was obtained (1) across professional groups and trainers and trainees, (2) in separate analyses for trainers and trainees, (3) in successive administrations of the scale, and (4) in surgical, anaesthetic and nursing groups analyzed separately. In the operating department practitioners group, Situation Awareness and Vigilance and Cooperation and Team Skills exhibited lower reliability. CONCLUSIONS: Assessment of surgical nontechnical skills is becoming a training priority. The present evidence suggests that the revised NOTECHS scale exhibits good reliability. Further empirical research should assess the validity of the scale.